Optimum cultural conditions of the Labyrinthula sp. strain HL78 in stiff media - Hien, Hoang Minh; Nam, Hoang Sy; Hong, Dang Diem (Academia Journal of Biology, 2014)
In this paper, the Labyrinthula sp. strain HL78 was isolated from leaves floating on the seawater at the coastal area of Halong bay, Quangninh province. This strain has the high growth rate and long chain polyunsaturated fatty acid (LCPUFA) production. The main fatty acid composition of this strain was: C12: 0 (15.3%), C16: 0 (12.8%), C18: 1 (3.4%), C18: 2 (12.2%), C20: 5n-3 (3.8%), C22: 5n-6 (7.3%) and C22: 6n-3 (11.5%). The ratio of LCPUFA to the total of fatty acids was 22.6%. The effects of various cultural conditions such as bacteria, sources of cacbon and nitrogen, oil concentrations, temperature, pH, salt concentrations (NaCl)... on the cell growth and the LCPUFA contents were tested. As the previous report of Hoang Lan Anh et al., (2005), the basic medium for the isolation of isolated Labyrinthula sp., GPYA medium, contained glucose (2 g/l), polypepton (1 g/l), yeast extract (0.5 g/l) and agar (10 g/l) in a 50% salt concentration of ASW (50% ASW, approximately 1.5% NaCl). For the cultivation of the isolated Labyrinthula sp. strain HL78, therefore, we used PYA-SBO or PYA-SBL medium which contained soybean oil (SBO) or soybean lecithine oil (SBL) (5 g/l) instead of the glucose in GPYA medium. GPYA medium without agar was called GPY medium. A bacterial suspension (100 ml, containing 50 mg of cell dry weight which have grown in the GPY medium) was spread on the PYA-SBO medium. The obtained results in this present allowed us to conclude that the optimum conditions for the cultivation of the Labyrinthula sp. strain HL78 were the PYA-SBO (or SBL) medium using the bacterial suspension of Psychrobacter phenylpyruvicus as a stimulating element for the growth of Labyrinthula, at pH from 7.5 to 8.0 and at temperature of 28oC.